Statin treatment is not associated with an increased risk of adrenal insufficiency in real-world setting - Maumus-Robert, Sandy; Jarne-Munoz, Ana; Pariente, Antoine; Duroux, Thomas; Duranteau, Lise; Bezin, Julien (Frontiers in Endocrinology, 2023)
Introduction: Statins could reduce the synthesis of steroid hormones, thereby could cause adrenal insufficiency. We investigated this risk in a large nationwide database. Methods: We conducted a nested case-control study using a cohort of individuals affiliated to the French health insurance system in 2010, ≥18y and without adrenal insufficiency history. Each case had a first event of adrenal insufficiency between 2015 and 2017 and was matched to up to ten controls on age, sex, and prior treatment with corticosteroids. Statin exposure was measured over the five years preceding the index date, considering a six-month censoring lag-time. Association was estimated using a conditional logistic regression adjusted for confounders included in a disease risk score. Analyses were stratified on age, sex and corticosteroid history of use. Results: 4 492 cases of adrenal insufficiency were compared with 44 798 controls (median age 66y, 58% women), of which 39% vs. 33% were exposed to statins, respectively. No association between statin use and adrenal insufficiency was found when adjusting the model for confounders (adjusted odds ratio 0.98; 95% confidence interval 0.90-1.05). These results were consistent regardless of the exposure definition and stratifications considered. Conclusions: Statin-related adrenal insufficiency risk, if any, seems to be very limited and does not compromise the benefit of statin treatment.